MENINGKATKAN HASIL BELAJAR SISWA KELAS VII DALAM MENULIS TEKS DESKRIPSI MELALUI MEDIA AUDIO VISUAL - Ginting, Rini Br; Isman, Muhammad; Pane, Rosnauli (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The problem in this study is that the Indonesian language learning activities in class VII of SMP Negeri 27 Medan show that the learning activities of writing using audio-visual media are still low. The researcher himself is the main data collector in this study, using an observation sheet as an aid. The steps in the data analysis flow are data collection, data reduction, data presentation, and drawing conclusions. With a value of 63.6 in cycle I and 80.3 in cycle II, the results of the learning actions of Writing Using Audio-Visual Media in Indonesian Language Learning consistently increased in each cycle. The results of the study showed that instructors were more skilled in preparing Indonesian language learning implementation plans and the resources needed to produce descriptive texts were maximally available.